2021
DOI: 10.3390/app11052155
|View full text |Cite|
|
Sign up to set email alerts
|

Multi-Stage Dynamic Transmission Network Expansion Planning Using LSHADE-SPACMA

Abstract: This paper introduces a multi-stage dynamic transmission network expansion planning (MSDTNEP) model considering the N-1 reliability constraint. The integrated planning problem of N-1 security and transmission expansion planning is essential because a single line outage could be a triggering event to rolling blackouts. Two suggested scenarios were developed to obtain the optimal configuration of the Egyptian West Delta Network’s realistic transmission (WDN) to meet the demand of the potential load growth and en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…It can be a DC or AC optimal power flow-based model [16]. The AC model is more accurate compared with the DC model; however, it needs a higher computational burden [17][18][19].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be a DC or AC optimal power flow-based model [16]. The AC model is more accurate compared with the DC model; however, it needs a higher computational burden [17][18][19].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The heuristic methods give high-quality solutions, but they cannot guarantee optimal solutions [23,24]. The metaheuristic techniques need lower computational efforts than the mathematical techniques and are recommended for solving non-linear large-scale optimization problems [17,[25][26][27][28]. The main disadvantage of meta-heuristic techniques is that they must be carried out for several runs to reach optimal solutions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A value of ρ is chosen, and the value of π GOIC and π GOSP are calculated. Then, the initial values of D * IC,l and D * SP,k are calculated using Equations ( 27) and (32), respectively. The initial value of the procurement cost of the GO is calculated as…”
Section: The Initial Value Of the Go Incentive π *mentioning
confidence: 99%
“…Both strategies demonstrated that the dependence on new circuit locations to mitigate the increase in short-circuit current is not useful in some power systems [34,35]. Hence, embedding FCLs during G&TEP is essential.…”
Section: Robustness Measurementmentioning
confidence: 99%